ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH PROGRAM STUDI (PRODI) PIAUD DI STIT NU AL FARABI PANGANDARAN - IMAS MASITOH (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2018)
The PIAUD study program is one of the majors that has many interested people today. Because one of the requirements to be able to propose certification is completing undergraduate education, certainly the requirements according to study programs, namely the PIAUD for PIAUD teaching staff. This study used qualitative research methods and descriptive research. The results showed that, (1) out of the 13 students who were the subjects of the study, there was 1 student who chose the PIAUD Study Program owe to personal factors,2 students due to psychological factors, 1 student due to social factors, 5 students due to personal and cultural factors, 1 student due to social and cultural factors, 1 student due to personal and psychological factors, and there were 2 students due to psychological, social, and cultural factors; (2) the factors that most influence students that choosing PIAUD Study Program at STIT NU Al Farabi Pangandaran are personal and cultural factors, which are 5 students.Keywords: factor analysis, choosing study programs, PIAUD study programs.